2018
DOI: 10.1091/mbc.e17-06-0422
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular topography modulates actin dynamics and signaling in B-cells

Abstract: B-cell signaling activation is most effectively triggered by the binding of B-cell receptors (BCRs) to membrane-bound antigens. In vivo, B-cells encounter antigen on antigen-presenting cells (APC), which possess complex surfaces with convoluted topographies, a fluid membrane and deformable cell bodies. However, whether and how the physical properties of antigen presentation affect B-cell activation is not well understood. Here we use nanotopographic surfaces that allow systematic variation of geometric paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 64 publications
(82 reference statements)
1
32
0
2
Order By: Relevance
“…when cells encounter obstacles 10 . It has also been established that ridges of width comparable to fibers in the extracellular matrix (ECM) can alter actin dynamics significantly 9,11,12 and bias the localization of focal adhesions 13,14 . Thus, in vivo, the topography of the ECM, such as collagen networks 15,16 , is likely to modulate actin dynamics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…when cells encounter obstacles 10 . It has also been established that ridges of width comparable to fibers in the extracellular matrix (ECM) can alter actin dynamics significantly 9,11,12 and bias the localization of focal adhesions 13,14 . Thus, in vivo, the topography of the ECM, such as collagen networks 15,16 , is likely to modulate actin dynamics.…”
mentioning
confidence: 99%
“…In prior work we have shown that actin waves can be nucleated near, and guided along, periodic nanotopography, in a phenomenon termed esotaxis. Actin-wave guidance has been observed in cell types that exhibit distinct physiological functions and migration phenotypes, including Dictyostelium discoideum 11,12 , neutrophil-like HL60 cells 12 , B cells 9 , and breastcancer cell lines 17 . However, there are clear differences in the responses of each of these cell types to nanotopography.…”
mentioning
confidence: 99%
“…[52] Large and slow scales can also be explored thanks to the possibility of obtaining stable (in our experiments, months) topography modifications over large areas, by means of irradiation with low-magnification lenses. Such features allow to employ our setup to study biological phenomena that occur on the scale of a few tens of seconds and on the spatial scale of a cell, such as calcium signaling, e.g., which has been shown to be influenced by topographies.…”
Section: Doi: 101002/advs201801826mentioning
confidence: 92%
“…Small and fast scales can be reached thanks to the fast responsivity of the azopolymer and is greatly improved by two technical advantages of our approach: i) deformations occur at once and do not require laser scanning and ii) substrate stimulation and biological observation can be performed simultaneously. Such features allow to employ our setup to study biological phenomena that occur on the scale of a few tens of seconds and on the spatial scale of a cell, such as calcium signaling, e.g., which has been shown to be influenced by topographies …”
mentioning
confidence: 99%
“…Physical and chemical characteristics of the extracellular environment, such as rigidity, biochemical composition, and topography, have been shown to influence actin dynamics and associated cell behavior ( Discher et al , 2005 ; Doyle et al , 2009 ; Lu et al , 2012 ; Petrie and Yamada, 2015 ). One mechanism for this modulation is mechanosensing via focal adhesions ( Ketchum et al , 2018 ). In addition, actin waves respond when cells encounter obstacles ( Weiner et al , 2007 ).…”
Section: Introductionmentioning
confidence: 99%